(untitled) (Annals of Medical Research, 2021)
Aim: In the present study, we aimed to systematically evaluate the effects of gabapentin and pregabalin, which are believed to be safe and well-tolerated and have analgesic, anticonvulsant, and anxiolytic effects, in the treatment of neuropathic pain after spinal cord injury despite their high side effect profiles.Material and Methods: A literature search of numerous electronic databases was performed. A combination of key words was used to retrieve studies published until November 1, 2018 correlated with the point of interest. The key words used were as follows: “spinal cord injury,” “neuropathic pain,” “gabapentin,” and “pregabalin.” Studies that met the inclusion criteria and were Level of I clinical trials were included in the study. The included studies were statistically evaluated.Results: In total, 125,515 publications were retrieved using the aforementioned key words. 19 studies on the use of gabapentin and pregabalin for the treatment of neuropathic pain associated with spinal cord injury were retrieved through.Conclusion: Studies suggested that available treatment modalities did not provide satisfactory outcomes for patients with neuropathic pain related to spinal cord injury. However, gabapentin and pregabalin were preferred as the first-line drugs in the treatment of neuropathic pain. The efficacy of gabapentin in the treatment of neuropathic pain after spinal cord injury has only been investigated in a few recent studies; data in these studies are not sufficiently clear and will need further clarification.Keywords: Gabapentin; Neuropathic Pain; Pregabalin; Spinal Cord Injury.